YouTube for the environment characteristics, themes and communication approaches of Philippine biodiversity videos - Barroga-Jamias, Serlie; Salazar, Jose Marie L. (2014)
Digital and visual media such as YouTube videos could be powerful tools in communicating to the public about environment and biodiversity issues. They can provide a creative and engaging way for the younger generation to learn about the importance of biodiversity conservation and environmental accountability. Hence, this study is a preliminary yet pioneering study in the Philippines to content analyze 95 purposively sampled videos from YouTube featuring Philippine biodiversity and uploaded during the period January 2011 January 2013. Analyzed were the characteristics of the videos (classification, length, date and source of upload, languages, and characters), emerging themes, communication approaches, and viewership. Biodiversity is a major environmental concern in Southeast Asia where the Philippines is one of the 17 mega-diverse countries and where 34 of the world's recognized biodiversity hotspots are located.
The videos were viewed 19,759 times in 2011 and 37, 629 times in 2012-January 2013 or almost double. Almost half (42.11%) were about aquatic biodiversity. These run from 12 seconds to 49 minutes, with majority (62%) lasting for only about 5 minutes or less. Majority of the videos (54.74%) have been uploaded in 2012, especially in January, and 41 (43.16%) in 2011, especially in June. These events coincided with biodiversity national programs the discovery of new species in the country. The themes that surfaced in the videos were the following (in order): (1) environmental beauty/aesthetics; (2) species information; (3) species richness; (4) backlash/deterioration; (5) call for action; (6) environmental/ ecological research; (7) tourism; (8) conservation; (9) advertisement; (10) species extinction; (11) environmental protest and (12) climate change.
Keywords: Media literacy -- Periodicals; Internet videos (Youtube) -- Social aspects; Social media